2018
DOI: 10.18203/2319-2003.ijbcp20184858
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacovigilance study of antiretroviral therapy in HIV positive out patients at a tertiary care teaching hospital

Abstract: Background: Anti-Retroviral Therapy regimen (ART) is the only treatment option for treating the HIV positive patients for improving the immune system by increasing the CD4 cells. But eventually these medications lead to development of some Adverse Drug Reactions (ADRs) in seropositive patients under treatment.Methods: A prospective observational study was conducted for 6 months from March to August 2018 at ART Centre, Sri Venkateswara Ramnarayan Ruya Government General Hospital (SVRRGGH), Tirupati.Results: Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Most of the participants (56.1%) who experienced ADEs had CNS manifestations (dizziness, anxiety, nightmares, depression), while one-third (31.8%) of them reported suffering from fatigue, this is expected as most of the patients were on 1e regimen (efavirenz, lamivudine, tenofovir) that contains efavirenz. Comparison with other studies revealed variations in the most occurring ADEs, CNS-related ADEs were the main occurrences, in some studies, 7 , 10 while in others, dermatological events ranked first, then gastro-intestinal problems and neuronal events. 11 , 15 In another study conducted in Nigeria, digestive disorders including nausea and abdominal pain were the most common ADEs followed by insomnia.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Most of the participants (56.1%) who experienced ADEs had CNS manifestations (dizziness, anxiety, nightmares, depression), while one-third (31.8%) of them reported suffering from fatigue, this is expected as most of the patients were on 1e regimen (efavirenz, lamivudine, tenofovir) that contains efavirenz. Comparison with other studies revealed variations in the most occurring ADEs, CNS-related ADEs were the main occurrences, in some studies, 7 , 10 while in others, dermatological events ranked first, then gastro-intestinal problems and neuronal events. 11 , 15 In another study conducted in Nigeria, digestive disorders including nausea and abdominal pain were the most common ADEs followed by insomnia.…”
Section: Discussionmentioning
confidence: 74%
“…The prospective observational study mentioned above applied the WHO-UMC scale and it was found that 308 out of 369 events of ADR cases had “probable” relationships with suspected drugs. 7 Another study with the same design and scale assigned “certain” causality as the most common with a percentage of 29.8%. 10 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations